Structural, historical, and comparative perspectives - Qvortrup, Jens. (Bingley, UK : Emerald, 2009)
In this volume, guest editor Qvortrup brings together contributions representing structural, historical, and comparative perspectives on the study of children and youth. Here, childhood is conceived as a structural feature of society, subject to the stable and changing forces of the larger social context, and comparable across time and cultures. Such perspectives have been relatively under-represented in the "New Sociology of Childhood," which has tended both to stress children's agency, and to favour ethnographic methods of inquiry. The series editors are pleased to expand and enliven the foci of Sociological Studies of Children and Youth with this volume edited by the internationally renowned Danish Sociologist Jens Qvortrup, the first non-U.S. editor in the series' history.
Includes bibliographical references.
Description based on print version record.
Keywords: Children -- Social conditions; Age groups: children; Age groups: adolescents; Social Science -- Children's Studies